TET2 Overexpression in Chronic Lymphocytic Leukemia Is Unrelated to the Presence of TET2 Variations. (18th February 2014) - Hernández-Sánchez, María; Rodríguez, Ana Eugenia; Kohlmann, Alexander; Benito, Rocío; García, Juan Luis; Risueño, Alberto; Fermiñán, Encarna; De Las Rivas, Javier; González, Marcos; Hernández-Rivas, Jesús-María
Abstract : TET2 is involved in a variety of hematopoietic malignancies, mainly in myeloid malignancies. Most mutations of TET2 have been identified in myeloid disorders, but some have also recently been described in mature lymphoid neoplasms. In contrast to the large amount of data about mutations of TET2, some data are available for gene expression. Moreover, the role of TET2 in chronic lymphocytic leukemia (CLL) is unknown. This study analyzes both TET2 expression and mutations in 48 CLL patients. TET2 expression was analyzed by exon arrays and quantitative real-time polymerase chain reaction (qRT-PCR). Next-generation sequencing (NGS) technology was applied to investigate the presence of TET2 variations. Overexpression of TET2 was observed in B-cell lymphocytes from CLL patients compared with healthy donors ( P = 0.004). In addition, in CLL patients, an overexpression of TET2 was also observed in the clonal B cells compared with the nontumoral cells ( P = 0.002). However, no novel mutations were observed. Therefore, overexpression of TET2 in CLL seems to be unrelated to the presence of genomic TET2 variations.